Analisis Fatwa Majelis Ulama Indonesia Provinsi Jawa Barat terhadap Produk Pemasaran Eco Racing - Mustofa (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This study emerged from the concern of the Muslim community regarding the circulation of businesses that use a multi-level marketing system in the form of multi-level marketing for Eco Racing products. Due to this concern, the Indonesian Ulema Council (Majelis Ulama Indonesia=MUI) issued a fatwa to respond to this product. This research aims to analyze the istinbat method by the MUI to reduce disputes among the people in their worship and muamalah. This qualitative research uses a literature approach: examining the MUI fatwa decision using several fiqh literature and scientific articles related to the MUI istinbat method. The research results show that the decision of MUI in West Java Province needs a complete review of the Eco Racing marketing system and the Islamic concept of muamalah. It is due to two things, including the imperfect explanation from PT BEST management to the MUI fatwa commission in West Java Province regarding the mechanism for regulating the Eco Racing product sales and bonus system and the limited number of experts in the MUI fatwa commission by existing knowledge. It is needed to respond to the dynamic development of sharia economics in Indonesia, especially in West Java.